Migration phenomena and their influence in trans-cultural care within a hospital frame - Miguel Ángel Fernández Molina (Universidad de Alicante, 2012)
Migratory phenomena and their influence in trans-cultural care within the premises of a Spanish General Hospital are approached in the present study. 8.7% of the population registered in Spain is foreigner being Alicante the autonomy with the highest rate (19%). The close relationship between Nursing and Anthropology has proved useful to identify cultural differences among foreign patients admitted to hospital and, as a result, useful tools have furnished the hospital with regards to the most appropriate ways to respectfully handling and treating those various cultural differences. Availability of means is also analyzed and some interesting outcomes and recommendations have been reached by those professionals who are eager to acquire proficiency in cultural fields.